2017
DOI: 10.1093/annweh/wxx087
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Symptoms in Hospital Cleaning Staff Exposed to a Product Containing Hydrogen Peroxide, Peracetic Acid, and Acetic Acid

Abstract: Cleaning and disinfecting products consisting of a mixture of hydrogen peroxide (HP), peracetic acid (PAA), and acetic acid (AA) are widely used as sporicidal agents in health care, childcare, agricultural, food service, and food production industries. HP and PAA are strong oxidants and their mixture is a recognized asthmagen. However, few exposure assessment studies to date have measured HP, PAA, and AA in a health care setting. In 2015, we performed a health and exposure assessment at a hospital where a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 33 publications
(52 reference statements)
4
30
0
Order By: Relevance
“…20 We found that use of several specific disinfectants was associated with higher risk of COPD development; these included hypochlorite bleach (chlorine), hydrogen peroxide, alcohol, and quaternary ammonium compounds (commonly used for low-level disinfection of noncritical items, such as environmental surfaces) and glutaraldehyde (used for high-level disinfection). 31 Several of these exposures often occurred concurrently, and disentangling the role of each product was challenging. When studying combinations of exposure to specific disinfectants, we found the highest risks of COPD incidence among nurses exposed to hypochlorite bleach or hydrogen peroxide and in those combining these exposures with exposure to aldehydes.…”
Section: Discussionmentioning
confidence: 99%
“…20 We found that use of several specific disinfectants was associated with higher risk of COPD development; these included hypochlorite bleach (chlorine), hydrogen peroxide, alcohol, and quaternary ammonium compounds (commonly used for low-level disinfection of noncritical items, such as environmental surfaces) and glutaraldehyde (used for high-level disinfection). 31 Several of these exposures often occurred concurrently, and disentangling the role of each product was challenging. When studying combinations of exposure to specific disinfectants, we found the highest risks of COPD incidence among nurses exposed to hypochlorite bleach or hydrogen peroxide and in those combining these exposures with exposure to aldehydes.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited literature is available about the effect of the peracetic acid solution on metallic surfaces [18, 28] and further studies are needed. Additionally, some authors have reported adverse effects of exposure to peracetic acid in higher concentrations (2%) by hospital cleaning staff, such as work-shift eye and upper and lower airway symptoms [29], but no report is available for low concentration as 0.2% peracetic acid solution in dental use.…”
Section: Discussionmentioning
confidence: 99%
“…Disinfection is a major component of the general set of veterinary and sanitary measures that ensure a high level of sanitation in the meat processing industry To expand the range of antimicrobial agents, we have developed a formula of an innovative disinfectant, which includes environmentally friendly compounds such as hydrogen peroxide, acetic and peracetic acids. The use of these compounds for disinfection has become widespread in many countries around the world (Hawley et al, 2018;Stopiglia et al, 2011).…”
Section: Concentration %mentioning
confidence: 99%